Effect of Njangsa Oil Seeds (Ricinodendron heudelitii) on Expression of Stearoyl-coenzyme a Desaturase in Laying Hens - Besong , Samuel; Fosung, Celestine; Jones, Ayasha; Fondong, Vincent (International Journal of Poultry Science, 2011)
Pathogenesis of liver steatosis in laying hen remains poorly understood. However, it has been suggested that regulation of the expression of Stearoyl-Coenzyme A Desaturase-1 (SCD-1) may alter hepatic lipid metabolism and prevent liver steatosis in laying hens. SCD-1 is an integral membrane protein that catalyzes the biosynthesis of monounsaturated fatty acids required for the synthesis of triglycerides, cholesterol esters and phospholipids. This study was conducted to determine whether Njangsa Oil Seed (NOS) (Ricinodendron heudelotii) which is rich in polyunsaturated fatty acids, specifically omega-3 fatty acids can regulate the expression of SCD-1 gene and lower hepatic lipid accumulation in laying hens. The experiment was carried out with seventy-two white leghorn hens (24 months old) which were randomly assigned to three layer diet supplemented with 0%, 10% or 20% NOS for 6 weeks. The mRNA levels in SCD-1 gene was quantified using forward and reverse primers specific to chicken SCD-1 in real-time reverse transcription-PCR (RT-PCR) technique with SYBER Green detection. Histological studies with liver tissues were performed with oil red stain and electron transmission microscope. Results indicate that NOS supplementation at 10% level tended to increase (p>0.05) SCD-1 mRNA expression in hens. Histological examination revealed micro-vesicular fat accumulation in the liver of hen fed NOS diets, indicating that supplementation of NOS in the diet may not prevent development of fatty liver. Results from this study suggest that NOS supplementation may regulate genes involve in lipid biosynthesis but may not prevent liver steatosis.